SEXUAL SADISM AS EXPERIENCED BY LISBETH SALANDER IN STIEG LARSSON’S THE GIRL WITH DRAGON TATTOO - DEA ANISSA RAHMAT (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
SEXUAL SADISM AS EXPERIENCED BY LISBETH SALANDER IN STIEG LARSSON’S THE GIRL WITH DRAGON TATTOO Dea Anissa Rahmat English Literature, Faculty of Languanges and Arts, Surabaya State University dearbepe@gmail.com Drs. Much. Khoiri, M.Si English Literature, Faculty of Languanges and Arts, Surabaya State University much.khoiri@yahoo.com Abstrak Sadisme dalam seksualitas adalah perasaan gairah seksual yang disebabkan oleh pemberian rasa sakit, penderitaan, dan penghinaan kepada orang lain. Perilaku sadisme yang nampak secara langsung dan terang-terangan dalam pencapaian titik klimaks perilaku seks seseorang dapat dijadikan indikator bahwa orang tersebut mengalami penyimpangan. Penyimpangan seks dalam kasus sadisme sering mengalami penurunan signifikasi dan fungsi akibat perilaku menyimpang dalam berfantasi. Orang yang menjadi mitra atau objek yang dikenai perilaku sadis dalam hubungan seks belum tentu menjadi rekan yang bersedia. Jika kegiatan seks yang identik dengan perilaku sadis ini disetujui oleh kedua pihak ataupun hanya seorang saja, maka dapat diartikan pihak yang melakukan kegiatan tersebut mengalami kegagalan seksual secara normal dan perlu alternatif lain untuk mencapai titik klimaks. Misalnya, melakukan aktifitas kekerasan pada saat berhubungan. Dalam kajiannya, peneliti sengaja mengambil novel dengan judul The Girl With The Dragon Tattoo untuk menganalisis perilaku menyimpang dalam hubungan seks yang dialami oleh tokoh Salander. Teori yang digunakan untuk menganalisis perilaku menyimpang dalam tokoh utama dalam novel berasal dari teori Sigmund Freud tentang psikologi dan kepribadian. Dengan dilengkapi teori relevan, penelitian ini mengambil beberapa kutipan dalam novel yang mewakili perilaku menyimpang dalam seksualitas untuk dijadikan data dalam kajian peneliti. Hasilnya, perilaku menyimpang dalam seks ditunjukkan oleh tokoh Lisbeth Salander dalam novel memberikan dua hipotesis. Pertama, dalam novel muncul beberapa sadisme seksual yang terjadi pada rekan tokoh Bjurman yang teridentifikasi dari data berupa kutipan teksnya. Salander sebagai korban sadisme seksual dari pengacara rekan Nails Bjurman. Kedua, beberapa faktor yang berkontribusi Lisabeth Salander untuk melakukan sadisme seksual. Penelitian ini mencerminkan pengalaman deskriptif sampel perempuan yang terlibat dengan perilaku sadisme seksual beserta faktor-faktor yang berkontribusi dibaliknya. Keywords: Sexual sadism, sadistic behavior, The Girl with The Dragon Tattoo Abstract Sexual sadism is a feeling of sexual excitement resulting from administering pain, suffering, or humiliation to another person. When sadism becomes directly and overtly related to sexual gratification, they are considered perversions. Sexual sadism often experiences significant impairment or distress in functioning due to actual sadistic behaviors or sadistic fantasies. With regard to actual sadistic behavior, the person receiving the pain, suffering, or humiliation may or may not be a willing partner. Whether or not the partner is consenting, it is the very real suffering they are experiencing that is arousing to the sadist. This study examines Stieg Larsson’s The Girl With The Dragon Tatttoo, which is about sexual sadism as experienced by Salander. This study uses theory of sexual sadism and Sigmund Freud’s theory of Psychology and Personality. By using relevant theories, the study analyses the data—i.e. quotations from the novel that represent sexual sadism. The result of this analysis shows that sexual sadism experienced by Lisbeth Salander as reflected in Steig Larsson’s The Girl With The Dragon Tattoo can be described by two parts. First, it shows that there are several sexual sadism which occurs from her guardian Bjurman. Salander as a victim of sexual sadism from the guardian laywer Nails Bjurman. Second is to reveal the factors that contributed Lisabeth Salander to do sexual sadism. It is about a descriptive experiences of a sample of women who have been consensually involved with sexual sadism and factors that contribute to sexual sadism. Keywords: Sexual sadism, sadistic behavior, The Girl with The Dragon Tattoo INTRODUCTION In human sexual life, there are certain conditions of sexual disorder which consider as embarassing and dangerous situations from the society’s point of view. Normally, sexual activity is the union of the female and male’s genital and other sexual activity besides it is taken as “abnormal”. Few examples of sexual deviations are: homosexual, masochism, sadism, necrophilia, fetishism, etc (Barlow, 2009: 364). Sadism implies pleasure in inflicting. When sexual sadism is applied to show fantasies, urges or behaviors that involve real acts in which the suffering of another person is found sexually exciting. The essential feature of sexual become directly related sexual gratification. That sexual gratification it considered perversions. Sadism is a feeling of sexual excitement resulting from administering pain, suffering, or humiliation to another person. The pain, suffering, or humiliation inflicted on the other is real, it is not imagined and may be either physical or psychological in nature. A person with a diagnosis of sexual sadism is sometimes called a sadist. The name of the disorder is derived from the proper name of the Marquis Donatien de Sade (1740-1814), a French aristocrat who became notorious for writing novels around the theme of inflicting pain as a source of sexual pleasure. The sadistic acts performed or fantasized by a person with sadism often reflect a desire for sexual or psychological domination of another person. These acts range from behavior that is not physically harmful although it may be humiliating to the other person (such as being urinated upon), to criminal and potentially deadly behavior. Acts of domination may include holding or imprisoning the partner through the use of handcuffs, cages, chains, or ropes. Other acts and fantasies related to sexual sadism include paddling, spanking, whipping, burning, beating, administering electrical shocks, biting, urinating or defecating on the other person, cutting, rape, murder, and mutilation. Psychopathia Sexualis, later defined sadism as: